Prejudice and determinants regarding tuberculosis patients among medical students in Dalian, Northeast China: a cross-sectional study - Yi, Yaohui; Sun, Meng; Chen, Xu; Pan, Yuanping; Lu, Jiachen; Yu, Yingying; Dou, Xiaofeng; Zhou, Ling (Frontiers in Public Health, 2024)
Health workers play a central role in global tuberculosis (TB) elimination efforts. If medical students have prejudiced attitudes towards TB patients, this may make it difficult for them to provide effective health care to TB patients in their future roles as health workers. There is currently no research on prejudice toward TB patients among medical students in China. This study aimed to explore the current status of medical students' prejudice against patients with TB and its associated predictors.We conducted a cross-sectional questionnaire survey among medical students at a medical university in Dalian, Liaoning Province, Northeast China.Multiple logistic regression analysis was employed to determine the predictive factors of medical students' prejudice against patients with TB.Results: More than half (57.23%) of the medical students held prejudices against individuals with TB. Multivariate logistic regression analysis revealed that not receiving TB health education (OR: 2.12, 95% CI: 1.35-3.32), not knowing a person with TB (OR: 2.52, 95% CI: 1.39-4.56), and fear of TB/TB patients (OR: 6.79, 95% CI: 4.36-10.56) were identified as risk factors for medical students' prejudice against TB patients. Conversely, residing in rural areas (OR: 0.60, 95% CI: 0.38-0.95), agreeableness (OR: 0.82, 95% CI: 0.73-0.92) and emotional stability (OR: 0.90, 95% CI: 0.81-1.00) in the Big Five personality traits, and a better understanding of TB knowledge (OR: 0.58, 95% CI: 0.38-0.89) were identified as protective factors.In China, a considerable number of medical students still exhibit prejudice against patients with TB. Targeted interventions, such as incorporating TB health education into the core curriculum of medical students, are still needed and enhance their agreeableness and emotional stability. Furthermore, greater focus should be placed on medical students from urban backgrounds or those who harbor fear or do not know a person with TB.